Implementation Of The Talaqqî Method And The Yanbȗ'a Method In Improving Students' Tahsin Al-Qur'ân Skills - agung jaenudin; Ilzamudin; Kholid; Fitri Hilmiyati; Muhajir; Deni Iriyadi; Wasehudin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The ability to read the Qur’an accurately according to tajwid rules (tahsin al-Qur’an) is a fundamental competence in Islamic education. However, many students at the madrasah tsanawiyah level still experience difficulties in proper pronunciation, fluency, and application of basic tajwid rules. This study aims to analyze the implementation of the Talaqqî method and the Yanbū‘a method in improving students’ Qur’anic reading skills at MTs Darul Ma’rifah Rangkasbitung and MTs Daar el Azhar Rangkasbitung. This research employed a qualitative descriptive approach. Data were collected through observation, semi-structured interviews, and documentation involving Qur’anic teachers, school principals, and students. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, with triangulation to ensure data validity. The findings indicate that the Talaqqî method is effective in improving the accuracy of pronunciation, particularly in makhārijul ḥurūf and tajwid application, through direct teacher–student interaction and immediate correction. Meanwhile, the Yanbū‘a method contributes significantly to improving reading fluency and learning consistency through a structured and graded instructional system. The study concludes that both methods have complementary strengths, and their integrative application can enhance the overall quality of Qur’anic reading instruction in madrasah tsanawiyah.